An improved echo tracking algorithm for arterial distensibility measurements - Joseph, J.; Jayashankar, V. (2009 International Conference on Biomedical and Pharmaceutical Engineering, 2009)
Arterial distensibility is often measured by non-invasively detecting the change in artery diameter over a cardiac cycle. Traditional methods using B-mode images require considerable processing power and time. Here we present a method to extract the distensibility waveform from RF signals obtained by ultrasound interrogation of the carotid artery. We propose an automatic method that uses an adaptive threshold to track the desired number of echoes and measure the artery diameter accurately. The algorithm could be used along with single element transducer based ultrasound measurement systems as well as B-mode scanners. The performance is analyzed using data obtained using phantom models of the artery as well as from human volunteers.